A verification analysis of power quality and energy yield of a large scale PV rooftop. (November 2016) - Plangklang, B.; Thanomsat, N.; Phuksamak, T.
Abstract: The power quality and energy yield of a large scale PV rooftop power plant in Samut Songkhram province are analyzed and presented in this paper. The power quality is examined and analyzed from the measured data to comply with the Provincial Electricity Authority (PEA) standard in Thailand. The measured parameters used in this study are as follows: the RMS Voltage, Frequency, Total Voltage Harmonic Distortion (THDv), and Voltage ripple. Certain parameters of measured data are used to calculate the distributed power yield and then compared with the Homer program simulation respectively. The investigated PV rooftop system has the installed capacity of 987.84 kWp. From the monitoring results, it found that the highest power yield was 778.125 kW while the simulation result was 783 kW. Moreover, based on the PEA standard EN 50160 with the cumulative percentile at 95% for PV rooftop power plant, the measured data showed that the power quality of this power plant passed the PEA regulations for its distribution network connecting system.